Evaluación del impacto social de la intervención del proyecto Magap - Caders en el proyecto Fomento agrícola, acuícola y de gestión de la comercialización empresarial en el predio María Caridad como medio de desarrollo para la asociación de campesinos el progreso del río Tiwa en los últimos dos años - Borja Vásquez, María Mikaela (2015)
The present work treats on The Peasants' Association the Progress of Rio Tiwa located in the Property Maria Caridad in the Province of Manabí and its experience of development by means of the support and intervention of the Project MAGAP-CADERS in the Project “Agricultural, Aquatic Promotion and of Management of the Managerial Commercialization”. Inside this work the topic talks each other in specific of the social impact that took the project as average of development for the associates and its families and the visible change that is generated from the implementation of the same one inside the property. Fundamental aspects as the increase of the sources of employment, the inclusion, participation of the women, equity, sustainable, etc. are basic to achieve a finished work that includes all the topics that represent the development in this case and that are fundamental in the writing of this work of grade. With this work there are announced the benefits and weaknesses of the implemented Project and as this one achieved changes from the base of the association to extend the families of the property in general generating diverse benefits for all and all. It is necessary to take into consideration that the intervention of the project in spite of producing significant changes in the property leaves loose ends in certain aspects which will be treated to the length of this work. In this work we will be able to re-live through the experience of the associates with the project and visualize the results that the same one generated in the lives of the associates and its family